# Answer on Linear Algebra Question for Mike

Question #3804

Using Cramer's rule, solve the following system of linear equations:

x + 4y - 2z = 3

x + 3y = 1 - 7z

2x = 8 - 9y - z

Can you explain how to do it? Help please!

x + 4y - 2z = 3

x + 3y = 1 - 7z

2x = 8 - 9y - z

Can you explain how to do it? Help please!

Expert's answer

Need a fast expert's response?

Submit orderand get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

## Comments

## Leave a comment